Local Community Attitude towards Forest-Based Ecotourism Development in Arbegona and Nensebo Woredas, Southern Ethiopia - Bruktawit Gezahegn; Zerihun Girma; Megersa Debele (International Journal of Forestry Research)
Understanding local community awareness and attitude towards forest-based ecotourism welfare is an important input for policymakers to develop and implement sustainable forest resource management strategies. However, the local community’s awareness and attitude towards forest-based ecotourism development have been poorly assessed and documented in remote areas. To this end, the present study assessed the local community’s awareness and attitude in Arbegona and Nensebo woredas’ forests, southern Ethiopia, towards ecotourism development. Household and key informant interviews and focus group discussions were used to collect data. Results indicated that more than half (57.9%) of the respondents expressed a negative attitude towards forest-based ecotourism development. The educational status of the respondents, their age, presence of conservation measures, source of energy for household consumption, and biophysical and socio-cultural variations in the study sites are significantly associated with local communities’ attitudes that have been exhibited towards the development of ecotourism and conservation of forest resources. Creating awareness through persuasion and communication of new and well-suited information, promoting alternative livelihood options, encouraging local benefits from the conservation of forest resources, and compensating costs induced by wild animals can minimise negative attitudes, thereby contributing to the enhancement of local communities’ positive attitudes towards forest resource conservation.